(untitled) (BIRDEM Medical Journal, 2022)
Background: Acute symptomatic seizures are clinical seizures occurring in close temporal relationship with an acute central nervous system (CNS) insult, which may be metabolic, toxic, structural, infectious or inflammatory. Currently there is dearth of information on the epidemiology of acute symptomatic seizures among adult medical admissions in Bangladesh. This study was designed to determine the frequency of presentation and etiology of acute symptomatic seizures among adults. Methods: This was a cross-sectional study of adult patients admitted with new onset seizure under Neurology Department of BIRDEM General Hospital during the period of January 2019 to December 2020. Clinical assessment and relevant investigations were done and data were collected regarding their etiological diagnosis. Data were analyzed using statistical package for the social sciences (SPSS) version 23. Results: Total admission during the study period was 2920 and among them, 100 patients (male 62, female 38) were having their first symptomatic seizures giving a prevalence of 3.4%. They were between 18 to 82 years of age. The main etiology of acute symptomatic seizure was metabolic encephalopathy (42.0%) .It was followed by acute cerebrovascular disease (31.0%) and acute CNS infection (16%) . Acute cerebrovascular disease and metabolic encephalopathy were predominant causes of symptomatic seizure among the elderly and CNS infections among the middle aged adults. The majority (70.0%) of patients had generalized onset seizures. Focal seizures and focal to bilateral tonic clonic seazure were present in 22% and 8% of the patients respectively. Conclusion: This study showed that metabolic encephalopathy, acute cerebrovascular disease and CNS infections were the prominent causes of acute symptomatic seizures. Treatment strategies should aim for promt identification and management of these conditions as seizures may not recur when the underlying cause has been removed or the acute phase has elapsed. BIRDEM Med J 2022; 12(2): 99-105